Unmanned Stores and Interior Architecture - Mustafa Kucuktuvek (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Unmanned stores represent a revolutionary shift in the retail industry, integrating artificial intelligence (AI), computer vision, and the Internet of Things (IoT) to streamline operations and enhance customer convenience. By eliminating traditional checkout processes, these cashier-less stores introduce new challenges and opportunities for interior architecture. This study explores the spatial implications of unmanned retail environments, focusing on store layout, wayfinding strategies, and material selection through a comparative case study of leading unmanned stores. Findings indicate that the success of these stores depends on flexible spatial configurations, intuitive navigation, AI-driven personalization, and adaptive lighting systems that enhance the user experience. However, concerns regarding security, data privacy, and accessibility remain significant challenges. As retail automation continues to evolve, interior architects must develop human-centered design strategies that balance technology with usability. Future trends suggest that augmented reality (AR), biometric authentication, and sustainable materials will further redefine the design of unmanned retail spaces.